Menekan Angka Kesenjangan Sosial di Indonesia melalui Sustainable Development Goals Perspektif Ekonomi Islam - Hakim, Abdurrahman (Institut Agama Islam Bengkulu, 2020)
This paper aims to describe solutions to reduce social inequality in Indonesia. The use of Islamic economic principles is offered by the author because it has the appropriate value of justice and equity to solve problems arising from sustainable development. Even though it is oriented towards fulfilling the future, it turns out that the concept of sustainable development has not been able to become the solution expected by the community, especially those in remote and border areas. The research method used in this paper is library research. Sources of data use secondary data in the form of journals, books, newspapers, mass media, and online media. The results of this study provide recommendations to the public and government to make use of natural resources based on the basic principles of Islamic economics, namely ownership of Allah alone, freedom to utilize resources, and balance.